The Effect of Process Parameters on Machining Volume and Depth Of Cut In Turning Operation Of AISI 1040 Steel With Abrasive Water Jet - Kartal, Fuat; Gökkaya, Hasan (Pamukkale Üniversitesi, 2014)
Bu çalışmada, AISI 1040 çeliğinin aşındırıcı su jeti ile tornalanması esnasında işleme parametrelerinin kaldırılan talaş hacmime ve kesme derinliğine etkisi araştırılmıştır. Yapılan çalışmada deney sayısının en az olması için literatürde yapılmış olan çalışmalar göz önüne alınmış ve ön deneyler sonucu elde edilen tecrübelerle en uygun işleme parametre değerleriyle deneyler gerçekleştirilmiştir. Deneysel çalışmalarda pompa basıncı (350 MPa), aşındırıcı boyutu (Garnet formunda ve boyutu 80 mesh) ve nozul çapı (1.2 mm) sabit tutulmuştur. Ø 30 ve 240 mm ebatlarında 1040 çeliği, dört farklı aşındırıcı akış oranı (50, 150, 250 ve 350 gr/dak.), nozul mesafesi (2, 5, 8 ve 11 mm), nozul ilerleme miktarı (5, 15, 25 ve 35 mm/dak.) ve torna aynası deviri (25, 50, 75 ve 100 dev/dak.) işleme parametreleri değerlerinde işlenmiştir. Elde edilen bulgulara göre en yüksek talaş hacmi 5 mm/dak nozul ilerleme miktarında 1387,25 mm3 elde edilmiştir. En yüksek kesme derinliği ise 0,94 mm olarak 100 dev/dak torna aynası devrinde elde edilmiştir.

In this study the effect of processing parameters during turning of AISI 1040 steel with abrasive water jet on machining volume and depth of cut. In the study, in order to keep the experiment quantity low, former studies in literature were taken into consideration and therefore experiments were realized with processing parameters and experiences that are most suitable to pre-experiments. In experimental studies pump pressure (350 MPa), abrader dimensions (in garnet form and dimension 80 mesh) and nozzle diameter (1.2 mm) were kept constant. 1040 steel with dimensions of Ø 30 and 240 mm were processed at four different abrader flow rate (50, 150, 250 and 350 gr/min), nozzle distance (2, 5, 8 and 11 mm), nozzle feed rate (5, 15, 25 and 35 mm/min) and lathe chuck revolutions (25, 50, 75 and 100 rpm). According to the findings the most highly material removal rate of 5 mm / min nozzle feed rate 1387.25 mm3 in the amount has been achieved. The maximum depths of cut 0.94 mm spindle speed of 100 rpm were obtained.
Keywords: Abrasive water jet cutting; Turning; AISI 1040; Chip volume; Depth of cut.; Aşındırıcı su jeti; Tornalama; AISI 1040; Talaş hacmi; Kesme derinliği.